A Metastudy of Counselor Education and Supervision: An Analysis of Publication Characteristics From 2000 to 2019. (4th March 2021) - Johnsen, Sarah; Watson, Kristen; Erford, Bradley T.; Crockett, Stephanie A.; Byrd, Rebekah
Abstract : Patterns of articles published in Counselor Education and Supervision from 2000 to 2019 were reviewed, and analyses sought to identify trends over time in author characteristics (e.g., gender, work setting, leading individual contributors and universities) and article characteristics (e.g., type, topic, research design, sample size, participant type, statistical procedures used).